Marshall Mcluhan and Higher Music Education - Carruthers, Glen (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
The way in which Marshall McLuhan’s theories relate to teaching and learning broadly has garnered scholarly attention. It is surprising, though, given his impact on Schafer and others, that there is scant critical commentary on the implications of McLuhan’s theories for either mass music or higher music education. The present study is a step towards redressing this gap. The study concludes that McLuhan’s iconoclastic views have direct bearing on formal learning environments, like music schools, that struggle with notions of inclusivity and exclusivity, community music and concert music, improvisation and textual interpretation, even as they embrace timely and sweeping curricular reform.